Profile of Alopecia Areata in Children at Prof. Dr. I.G.N.G. Ngoerah General Hospital, Bali, 2021-2023 - Handika, Natalia Jennifer; Dwi Karmila, I Gusti Ayu Agung (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: The prevalence of alopecia areata in childhood is increasing yearly. Alopecia areata is often seen in daily practice among our patients, studies related to this disease are still limited and must be updated. This study aims to describe the clinical characteristics of pediatric patients diagnosed with alopecia areata at Prof. Dr. I.G.N.G. Ngoerah General Hospital Denpasar from 2021 to 2023. Purpose: This study is expected to be used for decision-making related to the management of alopecia areata in children. Method: This study is a quantitative descriptive study. The data used is secondary data from medical records with a cross-sectional design. The sample includes pediatric patients diagnosed with alopecia areata at Prof. Dr. I.G.N.G. Ngoerah General Hospital Denpasar from January 2021 to November 2023. Results: This study involved 18 patients with an average age of 10.33 ± 4.85 years. In 2021, there were 5 patients; in 2022, there were 6 patients; and in 2023, there were 7 patients. The genders of girls and boys were the same, with 9 patients for each. Hair loss is the most common clinical symptom, with a percentage of 100%. The highest onset occurs between 1–6 months at 44.44%. The most common dermoscopic findings is a black dot, which accounts for 38.89%. Conclusion: Alopecia in childhood is different from alopecia in adults. The clinical picture in children can vary, and sometimes with nail involvement. Children with alopecia areata need further evaluation for other comorbidities.